Conventional and Unconventional Approaches to Exchange Rate Modeling and Assessment - Alquist, Ron; Chinn, Menzie D. (My University, 2006)
With a new approach, the authors examine the relative predictive power of the sticky price monetary model, uncovered interest parity, and a transformation of the net exports variable.